Dusza na wygnaniu - metamorfozy samotności w powieści Gajto Gazdanowa "Nocne drogi" = So ul in Exile -The Metamorphoses of Loneliness in Gajto Gazdanov's novel "Night Roads" - Kotin, Andrej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is concerned with the problem of social and existential alienation of an individualin a foreign cultural and geographical space as portrayed in the novel of Gajto Gazdanov "Night Roads". The protagonist is a young Russian emigrant who had to leave his homeland because of the Bolshevik Revolution.
Keywords: Gazdanow, Gajto Iwanowicz (pisarz rosyjski; 1903-1971); literatura rosyjska; proza rosyjska; motywy francuskie; 20 w.